Metastatic disease of the nervous system - Schiff, David; Van den Bent, Martin J. (Handbook of clinical neurology, 2018)
Section I. Overview -- Overview of metastatic disease of the central nervous system -- Section II. Brain metastases -- Brain metastases: epidemiology -- Pathogenesis and biology -- Role of the blood-brain barrier in metastatic disease of the central nervous system -- Metastatic diseases of the central nervous system - neuropathological aspects -- Brain metastasis: clinical manifestations, symptom management and palliative care -- Brain metastases: neuroimaging -- The role of surgery for brain metastases from solid tumors -- Brain metastases: fractionated whole brain radiotherapy -- Brain metastases: radiosurgery -- Systemic therapy for brain metastases -- Neurocognitive aspects of brain metastasis -- Section III. Other nervous system metastases -- Leptomeningeal metastasis -- Intracranial dural, calvarial and skull base metastases -- Epidural and intramedullary spinal metastasis: clinical features and role of fractionated radiotherapy -- Management - spinal metastases -- Plexus and peripheral nerve metastasis